Total Talar Prosthesis and Related 3D Technology: The State of the Art in Hindfoot and Ankle Reconstructive Surgery - Chayanin Angthong (Journal of Foot and Ankle Surgery (Asia Pacific), 2023)
Total talar prosthesis is a state-of-the-art implant in the field of foot and ankle surgery. It has been in constant development for over four decades. Nowadays, its design, manufacturing techniques, and raw materials tend to result in a prosthesis that mimics the natural anatomical function and allows for personalized profiles, which leads to superior outcomes compared to the previous generations. Although several improvements in prosthesis manufacturing have been proposed, ongoing enhancements are still necessary to improve the overall outcome following prosthesis replacement. Here, we delineate and discuss the latest concepts, treatment outcomes, and other details concerning total talar prosthesis and related three-dimensional (3D) manufacturing technologies based on the author's experiences and current literature.
Keywords: Foot and Ankle Surgery; Tendon Structure and Treatment; Orthopedic Surgery and Rehabilitation